2003
DOI: 10.1053/joca.2002.0867
|View full text |Cite
|
Sign up to set email alerts
|

Topographical analysis of the structural, biochemical and dynamic biomechanical properties of cartilage in an ovine model of osteoarthritis

Abstract: This study has highlighted the variable response of AC in different topographical regions of meniscectomized joints to the altered mechanical stresses introduced by this surgical procedure. The AC at the joint margins, while thicker and richer in PG, was found to be biomechanically softer (lower shear modulus) than normal AC, and because of this, would be expected to undergo degenerative changes with time leading to the onset of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
156
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 38 publications
20
156
3
Order By: Relevance
“…The aggrecanase-selective inhibitor delayed (by ~4 days) and reduced loss of the dynamic compression modulus, but did not substantially alter loss of the equilibrium compression or dynamic shear moduli. These data are consistent with previously published findings that the dynamic material properties of cartilage depend upon collagen content (Appleyard, et al, 2003). Recent work in our lab, however, also demonstrated significant correlations between aggrecan contents and the dynamic shear and compression properties in IL-1-stimulated cartilage (Palmer, et al, 2005), and the improved retention of explant aggrecan content by a non-selective metalloproteinase inhibitor observed here may contribute to protection of dynamic material properties.…”
Section: Discussionsupporting
confidence: 93%
“…The aggrecanase-selective inhibitor delayed (by ~4 days) and reduced loss of the dynamic compression modulus, but did not substantially alter loss of the equilibrium compression or dynamic shear moduli. These data are consistent with previously published findings that the dynamic material properties of cartilage depend upon collagen content (Appleyard, et al, 2003). Recent work in our lab, however, also demonstrated significant correlations between aggrecan contents and the dynamic shear and compression properties in IL-1-stimulated cartilage (Palmer, et al, 2005), and the improved retention of explant aggrecan content by a non-selective metalloproteinase inhibitor observed here may contribute to protection of dynamic material properties.…”
Section: Discussionsupporting
confidence: 93%
“…The superficial zone in the peripheral region contained smaller, flatter chondrocytes and a thicker zone of larger-diameter tangential fibers, while the central region contained larger, rounder cells and a thinner tangential fiber zone. While not specific to local thickness variations or spatial variations in cartilage morphology, biological and mechanical properties have been related to specific regions of cartilage [32][33][34][35][36][37][38] . For healthy cartilage, it has been shown that highly loaded regions show increased thickness and enhanced mechanical properties, while infrequently loaded regions show cartilage with degraded properties, including fibrillation, relative to loaded regions, even in relatively young subjects 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Water content was analyzed using previously described methods (20,21). Briefly, 56 cartilage explants were used for the determination of water content.…”
Section: Mechanical Injurymentioning
confidence: 99%